Economic Report on Africa 2010 - Nations Unies (United Nations, 2010)
The report focuses on how the recent global economic downfalls have compounded the unemployment rates in most African countries, thus also hindering real economic growth. Organized into two sections, ERA 2010 dissects the current unemployment trajectory citing both macro and microeconomic contributing factors. Additionally, the publication stresses on establishing the current economic climate as a learning tool for developing a comprehensive development planning framework.